Effects of Electrode Velocity Variations and Selection of Electric Current Against Quality Welding Results Mild Steel on SMAW Welding - Yohanes, Yohanes; Harahap, Muhammad Alhafih (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
One of the welding technology is SMAW (Shielded Metal Arc Welding) has its own advantages, such as, the current as the heat source used can be varied, easy to be used in various welding positions, penetration and the electrode width of welding can be adjusted. In order for proper welding speed, this research uses SMAW welding machine with sliding adaptive vertical system that varies the flow and welding speed to the welding characteristics, by doing visual observation and mechanical properties using tensile test. The welding speed is controlled using arduinouno with stepper motor rotation as the driving force. The material used is mild steel which has been tested for its composition content, the groove used is single V groove with 60° and electrode used is E6013 electrode. The number of specimens varied by 9 specimens with the highest tensile strength is 543,48 MPa and the lowest value is 253,75 MPa. Micro welding structure is determined by many factors including heat input, current strength, welding speed, and cooling rate. In this study the HAZ area has a larger grain structure than base metal and weld metal